Deepana and Pachana activities of Pippali and Pippalimula (fruits and roots of Piper longum L.) and its effects on digestive enzymes of albino rats - Gayatri H Phadke; Mukeshkumar Nariya
Pippali and Pippalimula are different parts of the plant Piper longum L. that belongs to the Piperaceae family. They have diversity in their Rasapanchaka (five attributes of drug) and hence may possess dissimilar pharmacological actions. This research study has been carried out to explore and compare the effects of these drugs on Deepana-Pachana activity, metabolic enzymes and hormones secreted in the gastrointestinal tract of albino rats. The effects of test drugs were assessed on food and water intake, food conversion ratio, gastric and intestinal enzymes and digestive hormones. Pippalimula showed significant results in body weight gain, water intake, as well as quantitative increase in amylase, lipase and trypsin levels in intestinal mucosa. While, Pippali demonstrated significant results in body weight gain and quantitative increase in Pepsin secretion in gastric mucosa of albino rats. Both the test drugs significantly increased food conversion ratio indicating improvement in digestion, metabolism, absorption and assimilation of food in albino rats. The findings underline that, Pippalimula has pronounced effects on intestinal digestive enzymes, while Pippali enhances the absorption and assimilation of food, indicating its Rasayana effect alongside Pippali$1 (Bs Deepana action. These differences reflect the unique modes of action of the two parts of Piper longum L. based on inherent qualities, thus supporting the Ayurvedic perspective of drug-specific therapeutic applications.s